GDF15 and ACE2 stratify COVID-19 patients according to severity while ACE2 mutations increase infection susceptibility - Torrens-Mas, Margalida; Perelló-Reus, Catalina M.; Trias-Ferrer, Neus; Ibargüen-González, Lesly; Crespí, Catalina; Galmes-Panades, Aina Maria; Navas-Enamorado, Cayetano; Sanchez-Polo, Andres; Piérola-Lopetegui, Javier; Masmiquel, Luis; Crespi, Lorenzo Socias; Barcelo, Carles; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Coronavirus disease 19 (COVID-19) is a persistent global pandemic with a very heterogeneous disease presentation ranging from a mild disease to dismal prognosis. Early detection of sensitivity and severity of COVID-19 is essential for the development of new treatments. In the present study, we measured the levels of circulating growth differentiation factor 15 (GDF15) and angiotensin-converting enzyme 2 (ACE2) in plasma of severity-stratified COVID-19 patients and uninfected control patients and characterized the in vitro effects and cohort frequency of ACE2 SNPs. Our results show that while circulating GDF15 and ACE2 stratify COVID-19 patients according to disease severity, ACE2 missense SNPs constitute a risk factor linked to infection susceptibility.